A novel anion-radical salt (N-Et-2.5-di-Me-Pz)(TCNQ)₂ (Pz is pyrazine) - Ziolkovskiy, D.V.; Kazheva, O.N.; Shilov, G.V.; Dyachenko, O.A.; Kravchenko, A.V.; Khotkevich, A.V.; Starodub, V.A. (Functional Materials, 2006)
Synthesis, structure and properties of the new tetracyanoquinodimethane anion-radical salt (ARS) having the composition (N-Et-2.5-di-Me-Pz)(TCNQ)₂ (Pz is pyrazine) are reported. The compound has a layered structure where conducting anion-radical layers formed by TCNQ alternate with non-conducting cation layers along the a axis. The charges of TCNQ particles in the stack alternate, i.e. are localized appreciably, which can account for a rather unusual temperature dependence of electric resistance. Such a peculiarity of structure renders to the ARS electronic system a somewhat two-dimensional character that is unusual for TCNQ ARS and agrees with the electrophysical measurements.